Analysis of International Transaction Systems and Methods of Payment in Indonesia - Fikri Ardiansyah; Ismi Hasanah; Tesalika; Khairani Alawiyah Matondang (International Journal of Asian Business and Management, 2022)
International transaction systems are often referred to as international payment systems. International payments are payments for transactions made by countries involved in international trade based on previously negotiated agreements. Payments in international trade are generally carried out through banks. This study uses a quantitative research method using secondary data which is indirectly obtained from the company, but the data is obtained from the internet site. This study aims to find out what the international transaction system is, how to do it and how to do international transactions and how to do it and how to pay in Indonesia